Implantation accuracy of novel polyimide stereotactic electroencephalographic depth electrodes—a human cadaveric study - Kullmann, Aura; Akberali, Farida; Van Gompel, Jaime J.; McGovern, Robert A.; Marsh, W. Richard; Kridner, Debra; Diaz-Botia, Camilo A.; Park, Michael C. (Frontiers in Medical Technology, 2024)
Stereoelectroencephalography (sEEG) is a minimally invasive procedure that uses depth electrodes stereotactically implanted into brain structures to map the origin and propagation of seizures in 1.61 ± 0.89 mm. Long trajectories (>50mm) had significantly larger EPEs and TPEs than short trajectories (<50mm), and no differences were found between orthogonal and oblique trajectories.Accuracies were similar or superior to those reported in the literature when using similar experimental conditions, and in the same range as those reported in patients.The results demonstrate that newly developed polyimide sEEG electrodes can be implanted as accurately as similar devices in the marker, without user errors when following the IFU, in a simulated clinical environment. The human cadaver ex-vivo test system provided a realistic test system, owing to the size, anatomy and similarity of tissue composition to that of the live human brain.